Telling Dreams: Shifting Child Images in Three Swedish Iconotexts - Dymel-Trzebiatowska, Hanna (INSTED: Interdisciplinary Studies in Education & Society, 2022)
The aim of the article is to reflect on transformations of the motif of a child’s dream fantasy in three Swedish iconotexts: I Skymningslandet [In the Land of Twilight] by Astrid Lindgren and Eva Billow (1949), Vilda bebin får en hund [The Wild Baby Gets a Puppy] by Barbro Lindgren and Eva Eriksson (1985), and Kivi & monsterhund [Kivi & Monsterdog] by Jesper Lundqvist and Bettina Johansson (2012). I focus on the functions and constructions of the protagonists’ fantasies to trace the representations of childhood as they were changing over the course of about 60 years. The three discussed iconotexts employ a similar narrative tool: an interplay of primary and secondary worlds based on the concept of a dream that may concurrently be interpreted as a real story, reflecting the shifting societal paradigms and aesthetics.